2019
DOI: 10.1177/1071100719864593
|View full text |Cite
|
Sign up to set email alerts
|

Fibular Nail Fixation: Topical Review

Abstract: Background: Intramedullary implants have been used historically in long bone fractures with success. In recent years, a variety of intramedullary implants for the treatment of fibular fractures have been investigated. These various implants have not been assessed together in a cohesive manner. In this review, we assess implants used for intramedullary fixation of fibular fractures with respect to implant design and clinical results. Methods: A comprehensive systematic literature review for intramedullary impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…In this study, Weber type C, pronation-type injury, and comminuted fracture of the fibula were found to be related to poor reduction at final follow-up in the IMN group, which is consistent with the results of previous studies. 4,5,18 This is thought to be caused by the failure of the IMN to provide sufficient stability for these types of injury as well as the initial poor reduction identified on 3D-reconstructed CT images. Bäcker and Vosseller 5 demonstrated that, in fibular fractures with proximal comminution, the IMN can piston or slide in the fibular shaft, eventually shortening the fibula due to its inherent limited axial stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, Weber type C, pronation-type injury, and comminuted fracture of the fibula were found to be related to poor reduction at final follow-up in the IMN group, which is consistent with the results of previous studies. 4,5,18 This is thought to be caused by the failure of the IMN to provide sufficient stability for these types of injury as well as the initial poor reduction identified on 3D-reconstructed CT images. Bäcker and Vosseller 5 demonstrated that, in fibular fractures with proximal comminution, the IMN can piston or slide in the fibular shaft, eventually shortening the fibula due to its inherent limited axial stability.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,18 This is thought to be caused by the failure of the IMN to provide sufficient stability for these types of injury as well as the initial poor reduction identified on 3D-reconstructed CT images. Bäcker and Vosseller 5 demonstrated that, in fibular fractures with proximal comminution, the IMN can piston or slide in the fibular shaft, eventually shortening the fibula due to its inherent limited axial stability. Kabukcuoglu et al 18 reported that fibular shortening and lateral displacement were observed in pronation-type comminuted fractures after the unlocked intramedullary device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the 4 patients with fibular nails did not need reoperations for soft tissue or lateral implant removal, which could be indicative of more favorable postoperative implant behavior, compared to the distal fibula plate. 1,11 When closing the lateral approach with a plate, it increases the tension in the deeper layers and decreases the coverage of the plate. Patients with a lateral approach who have a wound complication are more likely to have visible hardware with a plate, which results in more reoperations than if the osteotomy was fixated with a nail.…”
Section: Discussionmentioning
confidence: 99%
“…Plate fixation of fibula fractures can be complicated by wound dehiscence, infection, loss of fixation, and symptomatic implants in up to 20% of patients. 1,2 In patients with diabetes or vascular disease the risk of complication is even greater, with surgical site infections and wound healing issues being common. 1,3,4 In comparison, intramedullary nail (IMN) fixation of the fibula for ankle fractures results in less wound complications, less implant removals, and similar union rates and functional outcomes.…”
Section: Introductionmentioning
confidence: 99%